High-temperature-resistant neodymium-iron-boron rare earth permanent magnet waste regenerative magnet and preparation method thereof

CN122991843APending Publication Date: 2026-10-27GANZHOU ZHONGKE HUAXIANG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611341336.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

这些未被充分覆盖的晶粒会成为高温退磁的薄弱位置,使主相热稳定性的改善不能充分转化为磁体整体的耐高温性能

Benefits of technology

[0042]1、同构Co基体调控改善了再生磁体主相的高温稳定性。Co在适当含量下均匀进入2:14:1主相并占据部分Fe位,可以提高主相的居里温度,使磁体温度升高后仍能保持较强的磁交换作用,减缓剩磁和磁能积的下降。采用稀土和B比例与再生基体相匹配的Co富集母合金进行共同重熔,还可避免直接加入Co导致过渡金属比例过高、成分分布不均或软磁相析出。由此形成的Co改性主相为再生磁体提供了较稳定的高温磁性基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991843A_ABST
    Figure CN122991843A_ABST
Patent Text Reader

Abstract

The application discloses a high-temperature-resistant neodymium-iron-boron rare earth permanent magnet waste regenerative magnet and a preparation method thereof, relates to the technical field of rare earth magnetic materials, and belongs to the patent classification H01F1 / 00. First, waste is mixed with Co-rich alloy to smelt and rapidly quench, so that Co is replaced and solid-solved into a main phase to form a modified regenerative alloy containing R2(Fe,Co) 14 B; after powdering, neodymium hydride and metal gallium are added, magnetic field orientation pressing and liquid phase sintering are carried out, the amount of rare earth at the crystal boundary is supplemented by the neodymium hydride, the metal gallium is used to improve the spreading of the crystal boundary phase, and a continuous crystal boundary mass transfer network is constructed; then, crystal boundary diffusion and aging are carried out through a Tb-Cu gradient diffusion source layer. Through the cooperation of Co matrix regulation and Tb crystal boundary diffusion, the application supplements a continuous crystal boundary network to ensure that Tb is uniformly and deeply distributed, so that the regenerative magnet has high remanence, high coercivity and excellent high-temperature anti-demagnetization capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of rare earth magnetic materials technology, belonging to patent classification number H01F1 / 00, specifically to a neodymium iron boron rare earth permanent magnet waste recycled magnet and its preparation method. Background Technology

[0002] Neodymium iron boron (NdFeB) rare-earth permanent magnets possess high remanence, coercivity, and energy product, making them widely used in new energy vehicle drive motors, industrial servo motors, compressors, and high-temperature sensors. During magnet cutting, grinding, assembly, and equipment scrapping, a large amount of scrap, broken magnets, and decommissioned magnets are generated. These waste materials still retain significant amounts of NdFeB, praseodymium, iron, and boron, possessing high recycling value.

[0003] Neodymium iron boron (NdFeB) scrap has undergone sintering, aging, machining, and service processes, resulting in a significant difference in its internal structure compared to newly manufactured alloys. During processing and service, some active rare earth elements are fixed by oxygen, leading to a reduction or localized fracture of the original rare earth-rich grain boundary phase. Furthermore, re-powdering and sintering of the scrap may result in deviations in alloy composition, insufficient liquid phase at grain boundaries, and inhomogeneous main phase grain structure. These changes do not completely demagnetize the scrap, but they weaken the grain boundary isolation ability and high-temperature magnetic stability of the regenerated magnets.

[0004] As the temperature of a magnet increases, the magnetic exchange interaction and magnetocrystalline anisotropy of the main phase gradually weaken, leading to a decrease in remanence and intrinsic coercivity. If the thermal stability of the main phase itself is insufficient, the magnetic properties will decay rapidly with increasing temperature; if the anti-demagnetization capability at the outer edge of the grain is insufficient, reverse magnetic domains easily nucleate from the grain surface and extend into the grain interior. Therefore, high-temperature regenerated magnets not only require the main phase to maintain relatively stable magnetism at high temperatures, but also require the establishment of a sufficiently high anti-magnetization nucleation barrier at the outer edge of the grain.

[0005] When controlling the main phase and the outer edge of the grains separately, the continuity of the rare-earth-rich grain boundary phase inside the regenerated magnet becomes crucial to the effective synergy of these two control measures. When the rare-earth-rich grain boundary phase is insufficient or discontinuous, the elements used to strengthen the outer edge of the grains cannot uniformly enter the magnet interior along the grain boundaries, and some grains cannot form a complete, highly anisotropic outer edge region. These insufficiently covered grains become weak points for high-temperature demagnetization, preventing the improvement in the thermal stability of the main phase from being fully translated into the overall high-temperature resistance of the magnet.

[0006] Based on the above, the technical problem to be solved by the present invention is how to simultaneously improve the high-temperature stability of the main phase of the regenerated magnet and the anti-reverse magnetization ability of the outer edge of the grains, while making reasonable use of NdFeB rare earth permanent magnet waste and maintaining the balance of alloy composition, and solve the problem of discontinuous grain boundary transport channels caused by insufficient continuity of rare earth-rich grain boundary phase in the regenerated magnet, so that the two types of structure regulation effects can be effectively combined in the same regenerated magnet, thereby reducing the coercivity decay and irreversible demagnetization of the magnet under high temperature conditions. Summary of the Invention

[0007] The purpose of this invention is to provide a neodymium iron boron rare earth permanent magnet waste recycled magnet and its preparation method, so as to solve the technical problems mentioned in the background art.

[0008] To achieve the above objectives, the present invention provides the following technical solution:

[0009] A method for preparing a high-temperature resistant neodymium iron boron rare earth permanent magnet recycled magnet from waste materials includes the following steps:

[0010] Pretreatment and composition analysis were performed on NdFeB rare earth permanent magnet waste. Based on the analysis results, a Co-enriched composition-adjusting alloy was added to the pretreated waste, and the mixture was then smelted and rapidly solidified, so that at least some of the Co occupied R2Fe through substitutional solid solution. 14 Some Fe lattice sites in the B main phase yield R2(Fe,Co). 14 Co-modified recycled alloys with B as the main phase, wherein R is at least one of Nd and Pr;

[0011] The Co-modified recycled alloy was subjected to hydrogen crushing, dehydrogenation, and air jet milling in sequence to obtain the main alloy powder;

[0012] Neodymium hydride and metallic gallium are added to the main alloy powder, and after mixing, magnetic field orientation, pressing, hydrogen removal and liquid phase sintering are performed in sequence so that the Nd component and Ga component retained after hydrogen removal of neodymium hydride are mainly distributed in the grain boundary region, and a regenerated sintered blank is obtained.

[0013] A Tb-Cu gradient diffusion source layer is formed on the surface of the regenerated sintered blank. The Tb-Cu gradient diffusion source layer has a relatively Cu-rich region close to the regenerated sintered blank and a relatively Tb-rich region far away from the regenerated sintered blank. Then, grain boundary diffusion and aging treatment are performed to obtain a high-temperature resistant neodymium iron boron rare earth permanent magnet waste regenerated magnet.

[0014] Preferably, the pretreatment includes demagnetization and the removal of the metal plating, non-metallic coating and oxide layer from the surface of the waste material by dry grinding or planing.

[0015] The total residual amount of surface coatings in the pretreated waste is no more than 0.05 wt%, the total rare earth content is 29.5–31.5 wt%, the boron content is 0.90–1.10 wt%, and the oxygen content is no more than 0.35 wt%.

[0016] Preferably, the Co-enriched composition-adjusted alloy has a mass composition of Nd 30.50%, Co 15.00%, B 0.95%, and Fe 53.55%.

[0017] Let Cs be the measured mass fraction of Co in the pretreated waste, Cm be the mass fraction of Co in the Co-enriched composition-adjusting alloy, and Ct be the target mass fraction of Co in the Co-modified recycled alloy. Then, the ratio x of the Co-enriched composition-adjusting alloy to the total mass of the waste and the Co-enriched composition-adjusting alloy satisfies:

[0018] x=(Ct-Cs) / (Cm-Cs)

[0019] Of which, Ct is 1.60–2.00 wt%;

[0020] During co-smelting, the pressure inside the furnace is first reduced to no more than 5 Pa, and then argon gas is introduced to 30-60 kPa. The furnace is melted at 1350-1450℃ and held for 3-8 minutes. Then, the alloy strip with a thickness of 0.20-0.40 mm is cast by water-cooled copper rollers.

[0021] Preferably, the hydrogen crushing is carried out for 2 to 4 hours under the conditions of hydrogen absolute pressure of 0.08 to 0.15 MPa and temperature of 20 to 80°C; then, the hydrogen is removed for 1.5 to 2.5 hours under dynamic vacuum conditions at 520 to 580°C; and then the mixture is subjected to air jet milling in nitrogen or argon gas with oxygen and moisture content not exceeding 50 ppm to obtain a main alloy powder with D50 of 3.0 to 4.0 μm and D90 not exceeding 7.0 μm.

[0022] Preferably, based on 100 parts by mass of the main alloy powder, the amount of neodymium hydride added is 0.60 to 1.00 parts by mass, and the amount of metallic gallium added is 0.06 to 0.12 parts by mass;

[0023] Let rs be the measured total rare earth mass fraction of the main alloy powder, rt be the theoretical total rare earth mass fraction of the hydrogen-free solid before the liquid phase sintering and holding stage, h be the amount of neodymium hydride added, g be the amount of gallium added, wR be the measured rare earth mass fraction of the neodymium hydride raw material, and q be the solid retention rate of the neodymium hydride raw material after the hydrogen removal procedure. Then:

[0024] h=[100×(rt-rs)+rt×g] / (wR-rt×q)

[0025] Where rt ranges from 0.304 to 0.312;

[0026] When the neodymium hydride is stoichiometrically pure NdH2, wR=q=0.9862, then:

[0027] h=[100×(rt-rs)+rt×g] / [0.9862×(1-rt)]

[0028] Preferably, 5 to 10 parts by mass are taken from 100 parts by mass of the main alloy powder and mixed with all the neodymium hydride to form a carrier premix, and the carrier premix is ​​turned over in an inert atmosphere and at 38 to 42°C.

[0029] Molten gallium metal is fed into the controlled shear zone of the carrier premix in 4 to 6 portions through a heat-insulating ceramic capillary tube. After each addition, the mixture is mixed for 5 to 10 minutes, and after all the material is added, the mixture is mixed for another 10 to 20 minutes.

[0030] Cool the material to no higher than 10°C while maintaining the material turnover and solidify the metallic gallium. Then perform low-energy depolymerization and mix the resulting carrier premix with the remaining main alloy powder in a stepwise manner according to the geometric dilution method.

[0031] No organic carrier or dispersant is added during the mixing process. The mixed powder is sampled and tested from no less than 5 locations, and the relative standard deviation of the Ga content is no higher than 5%.

[0032] As a preferred option, the main alloy powder with added neodymium hydride and metallic gallium is oriented and pressed in a magnetic field of 1.8–2.2T, and then cold isostatically pressed at 180–220MPa;

[0033] The resulting compact is first subjected to hydrogen purging at 400–500℃ for 0.5–1 h, then at 680–720℃ for 1.5–2 h. After hydrogen evolution is complete and the furnace pressure returns to no more than 1 Pa, it is then heated at 5 × 10⁻⁶ ℃. -3 ~5×10 -2 Sintering at Pa and 1045–1060℃ for 2.5–3.5 h;

[0034] The thickness of the resulting regenerated sintered blank along the subsequent grain boundary diffusion direction shall not exceed 4 mm.

[0035] Preferably, the Tb-Cu gradient diffusion source layer is formed by dual-target magnetron sputtering of Tb and Cu targets, and includes a Tb60Cu40 sublayer, a Tb70Cu30 sublayer, and a Tb80Cu20 sublayer sequentially from the surface of the regenerated sintered billet outwards, wherein each number represents the atomic percentage of the corresponding element, and the thickness of the three sublayers is the same or differs by no more than 20%;

[0036] The total mass of the Tb-Cu gradient diffusion source layer is 0.65 to 0.80% of the mass of the regenerated sintered billet before deposition, and it is formed on at least two surfaces of the regenerated sintered billet that are arranged opposite each other along the shortest diffusion direction.

[0037] Preferably, when forming the Tb-Cu gradient diffusion source layer, the substrate vacuum of the magnetron sputtering system is no higher than 5 × 10⁻⁶. -4 Pa, working argon pressure is 0.3~0.8Pa, and the temperature of the regenerated sintered billet is not higher than 120℃;

[0038] After forming the Tb-Cu gradient diffusion source layer, at a value not exceeding 1×10 -2 Grain boundary diffusion was carried out at Pa and 880–890 °C for 9–12 h, followed by aging at 490–510 °C for 2–3 h.

[0039] After aging treatment, a residual layer of 0.02–0.05 mm is removed from the surface of the regenerated sintered billet, and saturation magnetization is performed along the original orientation direction using a pulsed magnetic field of not less than 4.5 T.

[0040] A high-temperature resistant neodymium iron boron rare earth permanent magnet waste recycled magnet is prepared by the above method.

[0041] Compared with the prior art, the beneficial effects of the present invention are:

[0042] 1. Isomorphic Co matrix modulation improves the high-temperature stability of the main phase of the regenerated magnet. When Co is uniformly incorporated into the 2:14:1 main phase at an appropriate content and occupies some Fe sites, it can increase the Curie temperature of the main phase, allowing the magnet to maintain strong magnetic exchange even at elevated temperatures, thus mitigating the decrease in remanence and energy product. Using a Co-enriched master alloy with a rare earth and B ratio matched to the regenerated matrix for co-remelting also avoids the problems of excessively high transition metal proportions, uneven composition distribution, or precipitation of soft magnetic phases caused by directly adding Co. The resulting Co-modified main phase provides a more stable high-temperature magnetic foundation for the regenerated magnet.

[0043] 2. Gradient Tb-Cu grain boundary treatment primarily enhances the ability of grain edges to resist demagnetization at high temperatures. When NdFeB magnets demagnetize, reverse magnetic domains typically nucleate near grain surface defects and grain boundaries. After entering the magnet along the grain boundaries, Tb is mainly distributed at the outer edge of 2:14:1 grains, giving this region a high local magnetocrystalline anisotropy field, thereby increasing the critical magnetic field required for reverse magnetic domain nucleation and propagation into the grain interior. The relatively Cu-rich region near the magnet in the gradient diffusion source layer helps improve grain boundary transport and magnetic isolation between grains, while the relatively Tb-rich region on the outer side continuously provides a Tb source. Since Tb is mainly concentrated at the grain edges rather than uniformly entering the entire grain, it can improve the intrinsic coercivity at high temperatures while reducing the adverse effects of heavy rare earth elements on the saturation magnetization and remanence of the grain core.

[0044] 3. When using Co matrix modulation in conjunction with Tb grain boundary diffusion, a key issue limiting their synergistic effect was identified: insufficient quantity and discontinuous distribution of rare-earth-rich grain boundary phases in the regenerated sintered body. During the initial processing, service, and re-powdering of recycled waste, some active rare earth elements are fixed by stable oxides, reducing the effective rare earth elements capable of participating in liquid-phase sintering and forming grain boundary films. Even if the Co-modified main phase achieves good high-temperature stability, discontinuous grain boundaries can still locally block the intergranular transport of Tb, resulting in inconsistent Tb diffusion depths and incomplete coverage of Tb-rich regions at the outer edges of grains. Insufficiently covered grains become weak points for high-temperature demagnetization, preventing the improvement in the thermal stability of the main phase from being fully translated into improved overall high-temperature resistance of the magnet. To address this issue of insufficient grain boundary continuity, neodymium hydride and gallium metal play complementary roles. Neodymium hydride (NdH2) provides an effective Nd component that can participate in liquid-phase sintering after a specified hydrogen removal process, quantitatively supplementing the rare earth source required to form rare earth-rich grain boundary phases, ensuring sufficient grain boundary phase material between grains. However, when only the Nd component is added, the newly added rare earth-rich phase may still form local aggregations at grain boundary junctions, and may not be able to spread uniformly into a continuous film. A small amount of gallium mainly tends to be distributed to the grain boundary region, which can adjust the interface state between the rare earth-rich liquid phase and the 2:14:1 grains, improving its spreading and filling ability. However, adding gallium alone can only improve the distribution state of the existing grain boundary phase, and cannot make up for the lack of grain boundary phase due to rare earth oxidation loss. Therefore, NdH2 solves the problem of "insufficient quantity" of rare earth-rich grain boundary phases, while gallium solves the problem of "insufficient spreading and connection" of grain boundary phases. When NdH2 and gallium are used together, the rare earth-rich grain boundary phase has sufficient formation quantity and can spread along the grain surface and connect the original discontinuous grain boundaries to form a thinner and continuous grain boundary mass transfer network. This continuous network provides a pathway for Tb to diffuse from the magnet surface inwards, enabling Tb to reach the outer edges of more Co-modified grains and reducing local diffusion interruptions and the absence of Tb-rich regions. The continuous non-main-phase grain boundary film also reduces direct magnetic exchange coupling between adjacent main-phase grains, further suppressing the cross-grain extension of the demagnetization region. Thus, the high-temperature magnetic stability provided by the Co-modified main phase and the high-temperature anti-demagnetization capability provided by the outer edges of Tb-rich grains correspond spatially, ultimately reducing the coercivity decay and irreversible flux loss of the magnet under high-temperature conditions. Attached Figure Description

[0045] Figure 1 This is a low-magnification SEM image of the neodymium iron boron rare earth permanent magnet waste regenerated magnet prepared in Example 1 of the present invention.

[0046] Figure 2 This is a high-magnification SEM image of the neodymium iron boron rare earth permanent magnet waste recycled magnet prepared in Example 1 of the present invention. Detailed Implementation

[0047] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0048] Example 1

[0049] A method for preparing recycled magnets from neodymium iron boron rare earth permanent magnet waste includes the following steps:

[0050] The NdFeB waste material that has been demagnetized and mechanically deplated was selected. Its mass composition is: Nd 24.955%, Pr 5.000%, Co 0.20%, B 0.92%, O 0.34%, with the balance being Fe and other original alloying elements. The residual amount of surface coating is 0.04%.

[0051] Based on a target Co content of Ct = 1.60%, the Co master alloy ratio is:

[0052] x=(1.60-0.20) / (15.00-0.20)=9.459%

[0053] 9.0541 kg of scrap and 0.9459 kg of Co master alloy were collected. The mass composition of the Co master alloy was 30.50% Nd, 15.00% Co, 0.95% B, and 53.55% Fe. The furnace charge was first evacuated to 4.5 Pa, then argon gas was introduced to 30 kPa, and melted at 1355℃ and held for 8 min. The melt was then processed into a thin strip with an average thickness of 0.20 mm using water-cooled copper rollers.

[0054] The thin strip was subjected to hydrogen absorption at an absolute hydrogen pressure of 0.08 MPa and a temperature of 20 °C for 4 h, followed by dynamic vacuum dehydrogenation at 520 °C for 2.5 h. The strip was then flow-milled in an inert gas atmosphere with oxygen and moisture content not exceeding 45 ppm to obtain a main alloy powder with a D50 of 3.0 μm and a D90 of 6.5 μm.

[0055] Take 10.000 kg of main alloy powder with a total rare earth mass fraction rs = 0.300064, add 60.0 g of neodymium hydride and 6.0 g of metallic gallium, i.e., h = 0.60 parts by mass and g = 0.06 parts by mass. Calculated based on pure NdH2, the theoretical hydrogen-free solid total rare earth mass fraction after hydrogen removal is:

[0056] rt=[100×0.300064+0.9862×0.60] / [100+0.06+0.9862×0.60]=0.304

[0057] 0.500 kg of the main alloy powder was taken and mixed with all the neodymium hydride to form a carrier premix, which was then turned over in an argon atmosphere at 38°C. Molten gallium was added in four portions through a ceramic capillary tube, mixing for 10 minutes after each addition, and continuing to mix for 20 minutes after all the gallium had been added. The mixture was kept turning over and cooled to 8°C. After confirming that the gallium had solidified and undergone low-energy depolymerization, it was then mixed with the remaining main alloy powder through geometric dilution. After the relative standard deviation of the Ga content reached no more than 5% according to multi-point testing, the mixture proceeded to the forming process.

[0058] The mixed powder was oriented and pressed in a 1.8T magnetic field, and then cold isostatically pressed at 180MPa. The pressed compact was first dehydrogenated at 400℃ for 1 hour, and then at 680℃ for 2 hours; after the furnace pressure was restored to 0.8Pa, it was then subjected to 5×10 -3 Sintering at 1045℃ for 3.5 h at Pa was used to produce a sintered blank with a thickness of 3.9 mm in the shortest diffusion direction.

[0059] At a substrate vacuum of 4.5 × 10 -4 Under conditions of Pa, working argon pressure of 0.3 Pa, and billet temperature not exceeding 90℃, Tb60Cu40, Tb70Cu30, and Tb80Cu20 sublayers of equal thickness were co-sputtered sequentially from the surface of the sintered billet outwards. The total mass of the diffusion source layer was 0.65% of the mass of the sintered billet, formed on two opposing large surfaces. Then, at 9×10⁻⁶ Pa, Tb60Cu40, Tb70Cu30, and Tb80Cu20 sublayers of equal thickness were sputtered. -3 Diffusion was carried out at 880℃ for 12 hours, followed by aging at 490℃ for 3 hours. After aging, a 0.02mm surface layer was removed by grinding, and the surface was saturated with a 4.5T pulsed magnetic field.

[0060] Example 2

[0061] A method for preparing recycled magnets from neodymium iron boron rare earth permanent magnet waste includes the following steps:

[0062] Pretreated NdFeB waste was selected, with the following mass composition: Nd 25.100%, Pr 5.160%, Co 0.50%, B 1.00%, O 0.20%, with the balance being Fe and other original alloying elements, and the residual amount of surface coating was 0.02%.

[0063] Based on a target Co content of Ct = 1.80%, the Co master alloy ratio is:

[0064] x=(1.80-0.50) / (15.00-0.50)=8.966%

[0065] Take 9.1034 kg of waste material and 0.8966 kg of Co master alloy. First, evacuate the furnace charge to 3 Pa, then fill it with argon gas to 45 kPa, melt it at 1400℃ and hold it for 5 min, and then make it into a thin strip with an average thickness of 0.30 mm by water-cooled copper rollers.

[0066] The thin strip was subjected to hydrogen absorption at an absolute hydrogen pressure of 0.12 MPa and a temperature of 50 °C for 3 hours, followed by dynamic vacuum dehydrogenation at 550 °C for 2 hours. The strip was then subjected to air jet milling in an inert gas atmosphere with oxygen and moisture contents not exceeding 30 ppm to obtain a main alloy powder with a D50 of 3.5 μm and a D90 of 6.5 μm.

[0067] Take 10.000 kg of main alloy powder with a total rare earth mass fraction rs = 0.302818, add 80.0 g of neodymium hydride and 9.0 g of metallic gallium, i.e., h = 0.80 parts by mass and g = 0.09 parts by mass. The theoretical total rare earth mass fraction of the hydrogen-free solid after hydrogen removal is:

[0068] rt=[100×0.302818+0.9862×0.80] / [100+0.09+0.9862×0.80]=0.308

[0069] 0.750 kg of the main alloy powder was taken and mixed with all the neodymium hydride to form a carrier premix, which was then turned over in an argon atmosphere at 40°C. Molten gallium was added in 5 portions, mixing for 8 minutes after each addition, and mixing for another 15 minutes after all the gallium was added. The mixture was kept turning over and cooled to 8°C. After confirming that the gallium had solidified, low-energy depolymerization and geometric dilution were performed. After the relative standard deviation of the Ga content reached no more than 5% according to multi-point testing, the mixture was ready for the forming process.

[0070] The mixed powder was oriented and pressed in a 2.0T magnetic field, followed by cold isostatic pressing at 200MPa. The pressed compact was first dehydrogenated at 450℃ for 0.75h, and then dehydrogenated at 700℃ for 1.75h; after the furnace pressure was restored to 0.5Pa, it was pressed at 2×10 -2 Sintering at 1052℃ for 3 hours under Pa conditions yielded a sintered blank with a thickness of 3.5 mm in the shortest diffusion direction.

[0071] Under a substrate vacuum of 3×10 -4 Under conditions of 0.5 Pa working argon pressure and billet temperature not exceeding 100℃, Tb60Cu40, Tb70Cu30, and Tb80Cu20 sublayers were co-sputtered sequentially from the surface of the sintered billet outwards. The total mass of the diffusion source layer was 0.725% of the mass of the sintered billet and covered the entire surface of the sintered billet. Then, at 8×10⁻⁶ Pa, Tb60Cu40, Tb70Cu30, and Tb80Cu20 sublayers were sputtered. -3 Diffusion was performed at 885℃ for 10.5 hours, followed by aging at 500℃ for 2.5 hours. After aging, a 0.035 mm surface layer was removed by grinding, and the surface was saturated with a 4.8T pulsed magnetic field.

[0072] Example 3

[0073] A method for preparing recycled magnets from neodymium iron boron rare earth permanent magnet waste includes the following steps:

[0074] Pretreated NdFeB waste was selected, with the following mass composition: Nd 25.564%, Pr 5.000%, Co 0.80%, B 1.08%, O 0.10%, with the balance being Fe and other original alloying elements, and the residual amount of surface coating was 0.01%.

[0075] Based on a target Co content of Ct = 2.00%, the Co master alloy ratio is:

[0076] x=(2.00-0.80) / (15.00-0.80)=8.451%

[0077] Take 9.1549 kg of scrap and 0.8451 kg of Co master alloy. First, evacuate the furnace charge to 4.5 Pa, then fill it with argon to 60 kPa, melt it at 1445℃ and hold it for 3 min, and then make it into a thin strip with an average thickness of 0.40 mm by water-cooled copper rollers.

[0078] The thin strip was subjected to hydrogen absorption at an absolute hydrogen pressure of 0.15 MPa and a temperature of 80 °C for 2 h, followed by dynamic vacuum dehydrogenation at 580 °C for 1.5 h. The strip was then subjected to air jet milling in an inert gas atmosphere with oxygen and moisture contents not exceeding 45 ppm to obtain a main alloy powder with a D50 of 4.0 μm and a D90 of 6.8 μm.

[0079] Take 10.000 kg of main alloy powder with a total rare earth mass fraction rs = 0.305589, add 100.0 g of neodymium hydride and 12.0 g of metallic gallium, i.e., h = 1.00 parts by mass and g = 0.12 parts by mass. The theoretical total rare earth mass fraction of the hydrogen-free solid after hydrogen removal is:

[0080] rt=[100×0.305589+0.9862×1.00] / [100+0.12+0.9862×1.00]=0.312

[0081] 1.000 kg of the main alloy powder was taken and mixed with all the neodymium hydride to form a carrier premix, which was then turned over in an argon atmosphere at 42°C. Molten gallium was added in 6 portions, mixed for 5 minutes after each addition, and mixed for another 10 minutes after all the gallium was added. The mixture was kept turning over and cooled to 8°C. After confirming that the gallium had solidified, low-energy depolymerization and geometric dilution were performed. After the relative standard deviation of the Ga content reached no more than 5% according to multi-point testing, the mixture was ready for the forming process.

[0082] The mixed powder was oriented and pressed in a 2.2T magnetic field, and then cold isostatically pressed at 220MPa. The pressed compact was first dehydrogenated at 500℃ for 0.5h, and then dehydrogenated at 720℃ for 1.5h; after the furnace pressure was restored to 0.8Pa, it was then subjected to 5×10 -2 Sintering at 1060℃ for 2.5 h at Pa was used to produce a sintered blank with a thickness of 3.9 mm in the shortest diffusion direction.

[0083] At a substrate vacuum of 4.5 × 10 -4 Under conditions of 0.8 Pa working argon pressure and a billet temperature not exceeding 115℃, Tb60Cu40, Tb70Cu30, and Tb80Cu20 sublayers of equal thickness were co-sputtered sequentially from the surface of the sintered billet outwards. The total mass of the diffusion source layer was 0.80% of the mass of the sintered billet and covered the entire surface of the sintered billet. Then, at 9×10⁻⁶ Pa, Tb60Cu40, Tb70Cu30, and Tb80Cu20 sublayers of equal thickness were sputtered. -3 The sample was diffused at 890°C for 9 hours, followed by aging at 510°C for 2 hours. After aging, a 0.05 mm surface layer was removed by grinding, and the sample was then saturated with a 5.0 T pulsed magnetic field.

[0084] Comparative Example 1: Except for not adding Co-enriched isomorphic master alloy and supplementing the furnace charge with an equal mass of NdFeB waste to prevent Co matrix control in the recycled alloy, the other raw materials, dosages and process parameters were the same as in Example 1.

[0085] Comparative Example 2: Except for using metallic Co to replace Co enrichment of the isomorphic master alloy and determining the amount of metallic Co added according to the target Co content of 1.60%, the other raw materials, dosages and process parameters are the same as in Example 1.

[0086] Comparative Example 3: Except for the absence of 0.60 parts by weight of neodymium hydride, the other raw materials, dosages and process parameters were the same as in Example 1.

[0087] Comparative Example 4: Except for the absence of 0.06 parts by mass of metallic gallium, the other raw materials, amounts and process parameters were the same as in Example 1.

[0088] Comparative Example 5: Except for the simultaneous omission of neodymium hydride and gallium metal, and the omission of the corresponding gallium metal pre-dispersion operation, the other raw materials, amounts and process parameters are the same as in Example 1.

[0089] Comparative Example 6: Except for replacing the three sublayers Tb60Cu40, Tb70Cu30 and Tb80Cu20 sequentially with a uniform diffusion source layer with an overall atomic ratio of Tb70Cu30, and keeping the total mass of the diffusion source layer unchanged, the other raw materials, amounts and process parameters are the same as in Example 1.

[0090] Comparative Example 7: Except for not forming a Tb-Cu gradient diffusion source layer, but still undergoing the same blank heat treatment as in Example 1 (holding at 880°C for 12 hours and aging at 490°C for 3 hours), the other raw materials, amounts, and process parameters were the same as in Example 1.

[0091] Performance testing

[0092] The sintered magnets prepared in Examples 1-3 and Comparative Examples 1-7 were processed into 10.00 mm × 10.00 mm × 4.00 mm samples, with the orientation direction and Tb-Cu grain boundary diffusion direction both along the 4.00 mm thickness direction. Tb-Cu gradient diffusion sources were placed on two opposite 10.00 mm × 10.00 mm surfaces, allowing the Tb-Cu component to diffuse inwards from both sides of the magnet along the thickness direction. The samples were machined to their final dimensions before the grain boundary diffusion treatment, and the two surfaces with diffusion sources were not ground after the diffusion treatment. Three parallel samples were prepared for each group, and the test results were taken as the arithmetic mean.

[0093] 1.20℃ Remanence Test

[0094] According to GB / T 3217—2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials", the magnetic properties of permanent magnet materials were tested using a closed magnetic circuit permanent magnet material magnetic performance tester. A pulsed magnetic field of not less than 5 T was applied along the orientation direction of the sample for saturation magnetization. After magnetization, the sample was allowed to stand at 20±1℃ for 30 min, and then placed in the closed magnetic circuit test device. The orientation direction of the sample was ensured to be consistent with the direction of the test magnetic field, and the BH demagnetization curve of the sample in the second quadrant was measured. The magnetic induction intensity corresponding to the applied magnetic field strength H being equal to 0 on the demagnetization curve was taken as the remanence Br20 of the sample at 20℃, in T.

[0095] 2.20℃ Intrinsic Coercivity Test

[0096] According to GB / T 3217—2013, the magnetic property tester should provide a maximum reverse magnetic field strength of not less than 3000 kA / m. The magnetic polarization J is calculated based on the measured magnetic induction intensity B and magnetic field strength H, using the following relationship:

[0097] J=B-mu0×H

[0098] In the formula, mu0 is the vacuum permeability, which has a value of 4π×10⁻⁷ H / m.

[0099] The JH demagnetization curve of the sample was obtained at 20±1℃. The reverse magnetic field strength corresponding to J equals 0 was determined by interpolation of adjacent test points. The absolute value of the reverse magnetic field strength was taken as the intrinsic coercivity Hcj20 of the sample at 20℃, with the unit being kA / m.

[0100] 3.20℃ Maximum Magnetic Energy Product Test

[0101] According to GB / T 3217—2013, the demagnetization curve BH in the second quadrant of the sample was obtained at 20±1℃. The magnetic induction intensity B and magnetic field intensity H on the demagnetization curve were calculated point by point, and the maximum absolute value of the product of B and H was taken as the maximum magnetic energy product.

[0102] The calculation relationship is as follows:

[0103] (BH)max = max(|B×H|)

[0104] The unit of maximum magnetic energy product is kJ / m³. This test uses the same sample, magnetic circuit, temperature, and clamping method as the remanence and intrinsic coercivity tests to reduce systematic errors caused by different test conditions.

[0105] 4.180℃ Intrinsic Coercivity Test

[0106] Following the demagnetization curve test principle specified in GB / T 3217—2013, a magnetic property tester for permanent magnet materials with a closed magnetic circuit and a high-temperature protective cavity was used. Independent parallel samples that had been saturated with magnetization and had not undergone other demagnetization tests were selected. The samples were placed in a high-purity argon protective cavity, and the sample temperature was monitored using a thermocouple adjacent to the sample surface. The samples were heated to 180±2℃, and after the sample temperature stabilized, it was held at that temperature for 15 min. Then, the JH demagnetization curve was measured at 180℃. The absolute value of the reverse magnetic field strength corresponding to J equaling 0 was taken as the intrinsic coercivity Hcj180 of the sample at 180℃, with units of kA / m.

[0107] 5. Remanence temperature coefficient test

[0108] According to GB / T 24270—2009 "Method for Measurement of Temperature Coefficient of Magnetic Properties of Permanent Magnet Materials", the remanence of the sample at 20℃ and 180℃ was measured in a closed magnetic circuit. Each temperature point should be measured only after the internal temperature of the sample has stabilized, and the sample clamping position, orientation direction and test magnetic circuit should be kept consistent.

[0109] The average temperature coefficient of remanence is calculated according to the following formula:

[0110] αBr=[Br180-Br20]÷[Br20×160]×100%

[0111] In the formula, αBr is the average temperature coefficient of remanence in the range of 20 to 180℃, in % / ℃; Br20 is the remanence of the sample at 20℃, in T; Br180 is the remanence of the sample at 180℃, in T; and 160 is the temperature difference between 180℃ and 20℃, in ℃.

[0112] The temperature coefficient of remanence is usually negative. The smaller the absolute value, the slower the remanence decreases as the temperature increases.

[0113] 6. Temperature coefficient test of intrinsic coercivity

[0114] According to GB / T 24270—2009, under the same closed magnetic circuit, temperature control conditions and sample clamping conditions, the intrinsic coercivity of the sample at 20℃ and 180℃ was determined respectively.

[0115] The intrinsic coercivity mean temperature coefficient is calculated according to the following formula:

[0116] βHcj=[Hcj180-Hcj20]÷[Hcj20×160]×100%

[0117] In the formula, βHcj is the average temperature coefficient of intrinsic coercivity in the range of 20 to 180℃, in % / ℃; Hcj20 is the intrinsic coercivity of the sample at 20℃, in kA / m; Hcj180 is the intrinsic coercivity of the sample at 180℃, in kA / m; and 160 is the temperature difference between 180℃ and 20℃, in ℃.

[0118] The temperature coefficient of intrinsic coercivity is usually negative. The smaller the absolute value, the slower the intrinsic coercivity decays with increasing temperature.

[0119] 7. Curie temperature test

[0120] The Curie temperature was determined according to GB / T 43870.1—2024, "Method for Measurement of Curie Temperature of Magnetic Materials—Part 1: Permanent Magnet Materials". A witness sample of 50±5 mg was taken from each group of magnets and measured using a thermomagnetic analyzer with a high-temperature accessory under argon protection with a purity of not less than 99.999%. A constant test magnetic field of 80 kA / m was applied to the sample, and the temperature was increased from 25℃ to 400℃ at a rate of 5℃ / min. The curve of magnetization intensity as a function of temperature was continuously recorded, and the Curie temperature Tc of the sample was determined according to the data processing method specified in GB / T 43870.1—2024. Independent samples were used for the Curie temperature test, and the tested samples were not used for other magnetic property tests.

[0121] 8.180℃ Irreversible Flux Loss Test

[0122] The sample was saturated with a pulsed magnetic field of not less than 5 T along the orientation direction and placed at 23±2℃ for 24 h. The initial magnetic flux Phi0 of the sample was measured using a calibrated Helmholtz coil and an electronic fluxmeter. Each sample was measured three times consecutively and the arithmetic mean was taken.

[0123] The sample, after initial magnetic flux measurement, was placed in a constant permeability aging fixture calibrated with a demagnetization curve and a permeability coefficient Pc of 2.00±0.05. It was heated to 180±2℃ under dry argon protection and held for 2 hours. After the holding period, the sample was removed from the fixture, cooled at 23±2℃, and allowed to stand for 2 hours. Without remagnetizing, the aging magnetic flux Phi1 was measured using the same Helmholtz coil, the same sample placement orientation, and the same measurement position.

[0124] Irreversible flux loss is calculated using the following formula:

[0125] Lirr=|Phi0-Phi1|÷|Phi0|×100%

[0126] In the formula, Lirr is the irreversible magnetic flux loss after being kept at 180℃ for 2 h, in terms of %; Phi0 is the initial magnetic flux measured before high-temperature aging; and Phi1 is the magnetic flux measured after the sample is kept at 180℃ for 2 h and then cooled to room temperature.

[0127] The smaller the irreversible flux loss value, the more effective magnetic flux the magnet can retain after high-temperature aging, and the better its high-temperature demagnetization resistance.

[0128] Table 1:

[0129] Example 1 1.189 2078 268.4 414 -0.103 -0.500 325 3.2 Example 2 1.181 2137 263.7 469 -0.099 -0.488 328 2.2 Example 3 1.169 2226 256.8 542 -0.096 -0.473 332 1.5 Comparative Example 1 1.183 1922 265.5 289 -0.116 -0.531 312 7.9 Comparative Example 2 1.158 1761 241.7 236 -0.108 -0.541 319 9.3 Comparative Example 3 1.169 1718 247.6 213 -0.106 -0.548 324 10.3 Comparative Example 4 1.182 1849 260.2 301 -0.104 -0.523 325 7.3 Comparative Example 5 1.153 1560 227.9 145 -0.107 -0.567 323 14.0 Comparative Example 6 1.191 1928 267.6 353 -0.103 -0.511 325 4.7 Comparative Example 7 1.204 1356 277.3 121 -0.102 -0.569 326 17.1

[0130] The synergistic effect of neodymium hydride (NdH) and gallium can be assessed using Examples 1 and Comparative Examples 3-5. Using Comparative Example 5 (without either NdH or gallium) as a baseline, adding gallium alone increased the intrinsic coercivity at 20°C from 1560 kA / m to 1718 kA / m, an increase of 158 kA / m; adding NdH alone increased it to 1849 kA / m, an increase of 289 kA / m. If the two effects are linearly superimposed, the intrinsic coercivity is 2007 kA / m, while Example 1, using both NdH and gallium, reaches 2078 kA / m, exceeding the linear superposition value by 71 kA / m. Using the same calculations at 180°C, the linear superposition value is 369 kA / m, while Example 1 reaches 414 kA / m, exceeding it by 45 kA / m. The linearity of the irreversible flux loss is approximately 3.6%, while in Example 1 it is 3.2%. The above results indicate that after neodymium hydride provides a sufficient amount of rare-earth-rich grain boundary phase, metallic gallium can further improve the spreading and distribution continuity of this grain boundary phase. When only metallic gallium is present, there is a lack of sufficient rare-earth-rich phase, and when neodymium hydride is added alone, local aggregation of the grain boundary phase is likely to occur. The combination of the two is more conducive to the formation of a continuous and thinner grain boundary isolation structure, thereby reducing the exchange coupling between adjacent main phase grains during high-temperature demagnetization.

[0131] The 2:14:1 isomorphic master alloy containing Co primarily improves the temperature stability of the main phase. Compared to Comparative Example 1 without this master alloy, Example 1 showed an increase in Curie temperature from 312°C to 325°C, an improvement in the remanence temperature coefficient from -0.116% / °C to -0.103% / °C, an increase in intrinsic coercivity at 180°C from 289 kA / m to 414 kA / m, and a decrease in irreversible flux loss from 7.9% to 3.2%. Although Comparative Example 2, which directly replaced the isomorphic master alloy with metallic Co powder, achieved a Curie temperature of 319°C, its room-temperature intrinsic coercivity and maximum energy product were lower than those of Example 1. This indicates that adding Co in the form of a pre-alloyed 2:14:1 phase is more conducive to the uniform entry of Co into the main phase lattice; directly adding fine Co powder easily leads to localized compositional segregation and cannot simultaneously ensure both the temperature stability of the main phase and the squareness of the demagnetization curve.

[0132] The gradient Tb-Cu diffusion structure primarily improves the utilization efficiency of Tb in the thickness direction of the magnet. Compared with Comparative Example 6, which uses a uniform Tb-Cu diffusion layer, Example 1 has remanences of 1.189 T and 1.191 T, respectively, which are essentially equivalent. Example 1 shows an increase of approximately 7.8% in intrinsic coercivity at 20°C and approximately 17.3% in intrinsic coercivity at 180°C, while the irreversible flux loss after holding at 180°C for 2 hours is reduced by approximately 31.9%. This demonstrates that the gradient Tb-Cu diffusion structure can improve the room-temperature coercivity and high-temperature demagnetization resistance of the magnet without significantly reducing remanence. Compared with Comparative Example 7, which does not involve Tb-Cu diffusion at all, Example 1 shows an increase in intrinsic coercivity at 20°C from 1356 kA / m to 2078 kA / m, while the irreversible flux loss is reduced from 17.1% to 3.2%. Although Comparative Example 7 exhibits high remanence and maximum energy product, its intrinsic coercivity at high temperatures is only 121 kA / m due to the lack of Tb-rich grain edges, indicating that high remanence cannot replace high-temperature demagnetization resistance. Gradient diffusion sources can alleviate the blockage of diffusion channels caused by excessive Tb enrichment in the near-surface region, allowing Tb to migrate more fully into the magnet interior and forming Tb-rich regions with high magnetocrystalline anisotropy at the outer edges of the main phase grains. Therefore, it has better high-temperature coercivity retention than a uniform diffusion source with the same total amount.

[0133] Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the essence and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a high-temperature resistant neodymium iron boron rare earth permanent magnet recycled magnet, characterized in that, Includes the following steps: Pretreatment and composition analysis were performed on NdFeB rare earth permanent magnet waste. Based on the analysis results, a Co-enriched composition-adjusting alloy was added to the pretreated waste, and the mixture was then smelted and rapidly solidified, so that at least some of the Co occupied R2Fe through substitutional solid solution. 14 Some Fe lattice sites in the B main phase yield R2(Fe,Co). 14 Co-modified recycled alloys with B as the main phase, wherein R is at least one of Nd and Pr; The Co-modified recycled alloy was subjected to hydrogen crushing, dehydrogenation, and air jet milling in sequence to obtain the main alloy powder; Neodymium hydride and metallic gallium are added to the main alloy powder, and after mixing, magnetic field orientation, pressing, hydrogen removal and liquid phase sintering are performed in sequence so that the Nd component and Ga component retained after hydrogen removal of neodymium hydride are mainly distributed in the grain boundary region, and a regenerated sintered blank is obtained. A Tb-Cu gradient diffusion source layer is formed on the surface of the regenerated sintered blank. The Tb-Cu gradient diffusion source layer has a relatively Cu-rich region close to the regenerated sintered blank and a relatively Tb-rich region far away from the regenerated sintered blank. Then, grain boundary diffusion and aging treatment are performed to obtain a high-temperature resistant neodymium iron boron rare earth permanent magnet waste regenerated magnet.

2. The preparation method according to claim 1, characterized in that, The pretreatment includes demagnetization and the removal of the metal plating, non-metallic coating and oxide layer from the surface of the waste material by dry grinding or planing. The total residual amount of surface coating in the pretreated waste is no more than 0.05 wt%, the total rare earth content is 29.5-31.5 wt%, the boron content is 0.90-1.10 wt%, and the oxygen content is no more than 0.35 wt%.

3. The preparation method according to claim 1, characterized in that, The mass composition of the Co-enriched alloy is 30.50% Nd, 15.00% Co, 0.95% B, and 53.55% Fe. Let Cs be the measured mass fraction of Co in the pretreated waste, Cm be the mass fraction of Co in the Co-enriched composition-adjusting alloy, and Ct be the target mass fraction of Co in the Co-modified recycled alloy. Then, the ratio x of the Co-enriched composition-adjusting alloy to the total mass of the waste and the Co-enriched composition-adjusting alloy satisfies: x=(Ct-Cs) / (Cm-Cs) Of which, Ct is 1.60–2.00 wt%; During co-smelting, the pressure inside the furnace is first reduced to no more than 5 Pa, and then argon gas is introduced to 30-60 kPa. The furnace is melted at 1350-1450℃ and held for 3-8 minutes. Then, the alloy strip with a thickness of 0.20-0.40 mm is cast by water-cooled copper rollers.

4. The preparation method according to claim 1, characterized in that, The hydrogen crushing is carried out for 2 to 4 hours under the conditions of hydrogen absolute pressure of 0.08 to 0.15 MPa and temperature of 20 to 80°C; then dehydrogenation is carried out for 1.5 to 2.5 hours under dynamic vacuum conditions at 520 to 580°C; and then air jet milling is carried out in nitrogen or argon gas with oxygen and moisture content not exceeding 50 ppm to obtain main alloy powder with D50 of 3.0 to 4.0 μm and D90 not exceeding 7.0 μm.

5. The preparation method according to claim 1, characterized in that, Based on 100 parts by mass of the main alloy powder, the amount of neodymium hydride added is 0.60 to 1.00 parts by mass, and the amount of metallic gallium added is 0.06 to 0.12 parts by mass; Let rs be the measured total rare earth mass fraction of the main alloy powder, rt be the theoretical total rare earth mass fraction of the hydrogen-free solid before the liquid phase sintering and holding stage, h be the amount of neodymium hydride added, g be the amount of gallium added, wR be the measured rare earth mass fraction of the neodymium hydride raw material, and q be the solid retention rate of the neodymium hydride raw material after the hydrogen removal procedure. Then: h=[100×(rt-rs)+rt×g] / (wR-rt×q) Where rt ranges from 0.304 to 0.312; When the neodymium hydride is stoichiometrically pure NdH2, wR=q=0.9862, then: h=[100×(rt-rs)+rt×g] / [0.9862×(1-rt)].

6. The preparation method according to claim 5, characterized in that, Take 5 to 10 parts by weight from 100 parts by weight of the main alloy powder and combine them with all the neodymium hydride to form a carrier premix. Turn the carrier premix over in an inert atmosphere and at 38 to 42°C. Molten gallium metal is fed into the controlled shear zone of the carrier premix in 4 to 6 portions through a heat-insulating ceramic capillary tube. After each addition, the mixture is mixed for 5 to 10 minutes, and after all the material is added, the mixture is mixed for another 10 to 20 minutes. Under the condition of keeping the material turning, the material is cooled to no higher than 10°C and the metallic gallium is solidified. Then, low-energy depolymerization is carried out, and the resulting carrier premix is ​​mixed with the remaining main alloy powder in a stepwise manner according to the geometric dilution method. No organic carrier or dispersant is added during the mixing process. The mixed powder is sampled and tested from no less than 5 locations, and the relative standard deviation of the Ga content is no higher than 5%.

7. The preparation method according to claim 1, characterized in that, The main alloy powder with added neodymium hydride and metallic gallium was oriented and pressed in a magnetic field of 1.8–2.2T and then subjected to cold isostatic pressing at 180–220MPa. The resulting compact is first subjected to hydrogen purging at 400–500℃ for 0.5–1 hour, then at 680–720℃ for 1.5–2 hours. After hydrogen evolution is complete and the furnace pressure returns to no more than 1 Pa, it is then heated at 5 × 10⁻⁶ ℃. -3 ~5×10 -2 Sintering at Pa and 1045–1060℃ for 2.5–3.5 h; The thickness of the resulting regenerated sintered blank along the subsequent grain boundary diffusion direction shall not exceed 4 mm.

8. The preparation method according to claim 1, characterized in that, The Tb-Cu gradient diffusion source layer is formed by dual-target magnetron sputtering of Tb and Cu targets, and includes Tb60Cu40 sublayer, Tb70Cu30 sublayer and Tb80Cu20 sublayer sequentially from the surface of the regenerated sintered billet outwards. Each number represents the atomic percentage of the corresponding element, and the thickness of the three sublayers is the same or differs by no more than 20%. The total mass of the Tb-Cu gradient diffusion source layer is 0.65 to 0.80% of the mass of the regenerated sintered billet before deposition, and it is formed on at least two surfaces of the regenerated sintered billet that are arranged opposite each other along the shortest diffusion direction.

9. The preparation method according to claim 8, characterized in that, When forming the Tb-Cu gradient diffusion source layer, the substrate vacuum of the magnetron sputtering system is no higher than 5 × 10⁻⁶. -4 Pa, working argon pressure is 0.3~0.8Pa, and the temperature of the regenerated sintered billet is not higher than 120℃; After forming the Tb-Cu gradient diffusion source layer, at a value not exceeding 1×10 -2 Grain boundary diffusion was carried out at Pa and 880–890 °C for 9–12 h, followed by aging at 490–510 °C for 2–3 h. After aging treatment, a residual layer of 0.02–0.05 mm is removed from the surface of the regenerated sintered billet, and saturation magnetization is performed along the original orientation direction using a pulsed magnetic field of not less than 4.5 T.

10. A high-temperature resistant neodymium iron boron rare earth permanent magnet waste recycled magnet, characterized in that, It is prepared by the method described in any one of claims 1 to 9 above.